ダイ10ジ ナンキョク チイキ カンソクタイ ウチュウセン ブモン ホウコク - 小倉, 紘一; オグラ, コウイチ; OGURA, Koichi (国立極地研究所, 1971)
P(論文) The 10th Japanese Antarctic Research Expedition carried out the following observations during the period of 1968-1970. The latitude dependence of cosmic-ray intensities was observed aboard the icebreaker FUJI along her route from Japan to Syowa Station, Antarctica, in 1968-1969. This latitude survey was made for three components, i. e., cosmic-ray neutron, meson and total ionizing components. For a month from January 14, 1969, simultaneous balloon observations of the geomagnetic conjugacy of auroral X-rays were attempted at Syowa Station and Keflavik, Iceland. Only three of ten Syowa flights completely coincided in time with some of the Keflavik flights, so that the overlapping observation time was about 20 hours. A number of examples of interesting auroral X-ray events were detected in all of the flights. The continuous observation of cosmic-ray neutron intensity was carried out using the 12-NM-64 neutron monitor with multiplicity meters after adding two neutron counters to the previous 10-NM-64 neutron monitor. The cosmic-ray unusual increase was observed on February 25 and again on March 30, 1969. Another balloon observation was made by using a BF_3 neutron counter in order to observe an altitude dependence of the low energy atmospheric neutron intensity at high latitudes. This report gives a brief summary of the above-mentioned observations and some preliminary results. departmental bulletin paper